Ethics for a breaking world: capabilities, intervention, responsibility, impartiality - Gómez, Oscar A. (Journal of global ethics, 2025)
The paper examines how the capability approach, as developed by Sen and Nussbaum, would fare as a guide for ethical reasoning when confronted with a catastrophic future. The analysis responds to Tim Mulgan’s Ethics for a Broken World, in which he imagines a world devastated by climate change and then investigates whether today’s philosophy would be of any help under those circumstances. In order to grasp how approaches would have to transform to deal with such a future, I modify Mulgan’s method from a comparative static (‘broken’) examination to a dynamic (‘breaking’) one. The capability approach is tested against problems related to justifying intervention, new conceptions of responsibility in the face of catastrophe, and dealing with demands of impartial attention to humanitarian needs. I suggest that the capability approach is useful in reflections about intervention and may also offer clues to deal with responsibility issues. However, impartiality problems seem beyond what the approach can handle at the moment, perhaps because of its close connection to the idea of justice. Giving more attention to the ethics of security is suggested as a possible way forward instead.